P233 Judicious use of oximetry can help deliver cost effective sleep service. (2nd December 2011) - Collins, C L; Balakrishnan, B; Madieros, J
Abstract : Background: Referrals to sleep service are increasing rapidly and make up to 30% of referrals to the Queen's Medical Centre campus of Nottingham Respiratory Department. Limited channel polysomnography (PSG) at home (PSH-H) or video (PSG_V) are time consuming and costly. In a retrospective study we assessed the role of oximetry in delivering cost effective sleep service. Methods: We reviewed new referrals to sleep clinic during February and March 2011. We aimed to quantify referrals, assess what investigations were done, the results of these and subsequent management. Cost analysis was then performed to assess impact of the tests ordered on service delivery. Costs of various tests at our centre are: oximetry £28, PSG-H—£ 200 and PSG-V—£350. Results: In February and March this year 79 new referrals were identified for snoring or sleep disturbance. 53 patients (67%) had oximetry as first test and 26 (33%) had PSG-H or PSG limited or video PSG. The two groups had similar baseline characteristics with BMI of and Epworth Sleepiness Scale (ESS) score of 11. Of those who initially had oximetry 15 (29%) went on to have PSG. Thus 52% of all referrals had PSG whereas 48% were managed with oximetry only. There was statistically significant correlation between 4% oxygen desaturation index per hour (4% ODI) and apnoea-hypopnoea index (AHI) obtained from PSG (R=0.96; p=0.05). The type of diagnostic test used had no impact on CPAP use. We see 600 new referrals per year. Had all patients been subjected to PSG it would cost the service £120 000 to £210 000 depending on the type of polysomnography requested. With nearly 50% patients managed with oximetry it would cost £68 400 to £113 000 leading to huge cost saving without compromising on the quality of service. Conclusion: Judicious use of oximetry can help deliver cost effective sleep service.